The Comparisons of Lavender and Jasmine Aromatherapy Effectiveness on Depression Level for Medical Students - Tania Lysandra Sukarman; Irna Permanasari Gani; Diana Krisanti Jasaputra (Berkala Ilmiah Kedokteran Duta Wacana, 2022)
Background Everyone can suffer from depression, including teenagers. Students in the medical faculty show higher depression levels than other faculties students due to being unable to adapt to the new daily activity as medical students. Lavender and Jasmine aromatherapy can reduce depression levels because it contains linalool.Objective The purpose of this research is to compare the effectiveness between Lavender and Jasmine aromatherapy on Maranatha Christian University medical student depression levels.Method This analytical research design used a simple random sampling method on 45 subjects divided into 3 groups: Lavender, Jasmine, and Control. The data measured was the total score of the BDI II (Beck Depression Inventory II) questionnaire before and after being given treatment for 1 week.Results The average BDI II score in the Lavender and Jasmine’s groups decrease from 19.73 (moderate depression) to 14.73 (mild depression) in the Lavender’s group and 19,33 (moderate depression) to 14.06 (mild depression) in Jasmine’s. There’s also decreased score in Control group, from 20.60 to 18.86 (mild depression).  Furthermore, data is converted into BDI II’s scores decrease percentage, 24.00% for Lavender’s group, 28.85% for Jasmine’s, and 5.80% for Control’s. Data were tested by the Kruskal Wallis test with significant results p=0.001 (p<0.05) followed by Mann-Whitney test.Conclusion Resume of this research is both Lavender and Jasmine aromatherapy has equal potential for reducing depression levels.Conclusion Resume of this research is both Lavender and Jasmine aromatherapy has equal potential for reducing depression levels.